Sharing reflections and expressing appreciation upon completing a decade as co-editor of the IJHPR - Bruce Rosen (BMC, 2021)
Abstract The Israel Journal of Health Policy Research (IJHPR) was launched in January 2012. In December 2021 it will be completing 10 years of continuous publication. I have had the privilege of serving as the journal's co-editor in chief during this period, and after ten years of service I am now preparing to step down from that role. IJHPR achievements of which I am particularly proud include remaining true to its mission, attracting manuscripts from virtually all the Israeli institutions engaged in health policy research as well as many leading institutions abroad, widening the circle of Israeli professionals who are submitting manuscripts to journals, and helping many established Israeli academics expand their repertoires to include articles with strong policy components. Several people and organizations have helped make editing the IJHPR such a wonderful experience for me. They include IJHPR co-editor Avi Israeli, IJHPR associate editor Steve Schoenbaum, the Israel National Institute for Health Policy Research (which sponsors the journal), BioMed Central (which publishes the journal), the Myers-JDC-Brookdale Institute (my employer), my family (and particularly my wife, Laura Rosen), and the thousands of authors who have chosen to publish with the IJHPR. May the journal's second decade be even better than its first one!